Quantification and reliability of [11C]VC - 002 binding to muscarinic acetylcholine receptors in the human lung — a test-retest PET study in control subjects - Cselényi, Zsolt; Jucaite, Aurelija; Kristensson, Cecilia; Stenkrona, Per; Ewing, Pär; Varrone, Andrea; Johnström, Peter; Schou, Magnus; Vazquez-Romero, Ana; Moein, Mohammad Mahdi; Bolin, Martin; Siikanen, Jonathan; et al. (EJNMMI research, 2020)
Background The radioligand [ 11 C]VC-002 was introduced in a small initial study long ago for imaging of muscarinic acetylcholine receptors (mAChRs) in human lungs using positron emission tomography (PET). The objectives of the present study in control subjects were to advance the methodology for quantification of [ 11 C]VC-002 binding in lung and to examine the reliability using a test-retest paradigm. This work constituted a self-standing preparatory step in a larger clinical trial aiming at estimating mAChR occupancy in the human lungs following inhalation of mAChR antagonists. Methods PET measurements using [ 11 C]VC-002 and the GE Discovery 710 PET/CT system were performed in seven control subjects at two separate occasions, 2–19 days apart. One subject discontinued the study after the first measurement. Radioligand binding to mAChRs in lung was quantified using an image-derived arterial input function. The total distribution volume ( V T ) values were obtained on a regional and voxel-by-voxel basis. Kinetic one-tissue and two-tissue compartment models (1TCM, 2TCM), analysis based on linearization of the compartment models (multilinear Logan) and image analysis by data-driven estimation of parametric images based on compartmental theory (DEPICT) were applied. The test-retest repeatability of V T estimates was evaluated by absolute variability (VAR) and intraclass correlation coefficients (ICCs). Results The 1TCM was the statistically preferred model for description of [ 11 C]VC-002 binding in the lungs. Low VAR (< 10%) across analysis methods indicated good reliability of the PET measurements. The V T estimates were stable after 60 min. Conclusions The kinetic behaviour and good repeatability of [ 11 C]VC-002 as well as the novel lung image analysis methodology support its application in applied studies on drug-induced mAChR receptor occupancy and the pathophysiology of pulmonary disorders. Trial registration ClinicalTrials.gov identifier: NCT03097380 , registered: 31 March 2017.